PENGEMBANGAN INSTRUMEN PENILAIAN AUTENTIK MATERI PERUBAHAN DAN PELESTARIAN LINGKUNGAN HIDUP PADA PEMBELAJARAN BIOLOGI DENGAN INQUIRY LEARNING KELAS X SMA` - Puji Sri Indarti; Darmawati Darmawati; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to produce an authentic assessment instrument of environmental change and conservation materials on biology learning with inquiry learning biology class X SMA. The research was conducted in Biology Education Campus of FKIP University of Riau and SMAN 2 Bangko Pusako in November 2017. The subject of this research is authentic assessment instrument of KD 3.11 material of environmental change and preservation. The way to analyze the authentic assessment instruments that teachers have made is to use assessment indicators. Assessment indicators are made according to the demands of the 2013 curriculum for each competency, both cognitively, affectively, psychomotorically. The result of analysis of authentic assessment instrument made by class X researcher for biology study of material change and environmental preservation in SMAN 2 Bangko Pusako can be seen that for written assessment test with average 3,26 with very valid category, attitude evaluation with average 3,36 with category is very valid, performance assessment with mean 3.56 with category very valid, assessment of project with mean 3.5 with category very valid, product rating with mean 3.5 with category very valid, self assessment with mean 3,42 with category very valid, portofolio assessment with average of 3.47 with very valid category.Key words: Authentic assessment, material change and environmental conservation,X-class biology teacher, SMAN 2 Bangko Pusako